A Self-Adaptive Back-off Optimization Scheme Based on Beacons Probability Prediction for Vehicle Ad-Hoc Networks - Zhao, Haitao; Du, Aiqian; Zhu, Hongbo; Li, Dapeng; Liu, Nanjie (China communications, 2016)
In order to improve the broadcast reception rates of beacon messages in vehicle ad-hoc networks,a conclusion that the relationship between collision probability and minimum contention window size and the relationship between expiration probability and minimum window size was reached by building a Markov model. According to this conclusion, a back-off algorithm based on adjusting the size of minimum contention window called CEB is proposed, and this algorithm is on the basis of the differential size between the number of expiration beacons and preset threshold. Simulations were done to compare the performance of CEB with that of RBEB and BEB, and the results show that the performance of the new proposed algorithm is better than that of RBEB and BEB.